Integrasi Zakat Dan Pajak Di Kota Binjai : Studi Kualitatif Tentang Persepsi Dan Impementasi Pada Wajib Pajak Muslim - Alwi Saparizhan; Muhammad Ramadhanu Jupri; Muhammad Nur Iqbal (CV. ITTC INDONESIA, 2026)
This study aims to analyze the relationship between zakat and taxation and to examine zakat management, public understanding, and challenges in the implementation of zakat as a tax deduction at the National Zakat Agency (BAZNAS) of Binjai City. Zakat and taxes are important instruments in promoting social welfare and supporting national development. Although they are based on different legal foundations, both serve a similar purpose, namely collecting funds for public benefit. In Indonesia, the relationship between zakat and taxation is reflected in policies allowing zakat paid through BAZNAS or government-authorized zakat institutions to be deducted from Taxable Income. This research employed a qualitative method with a descriptive approach. Data were collected through interviews, documentation, and literature studies related to zakat and taxation. The data were analyzed descriptively to provide a comprehensive understanding of the implementation of zakat as a tax deduction at BAZNAS Binjai City. The findings show that zakat management at BAZNAS Binjai City has supported the tax deduction policy through proper administrative systems, issuance of zakat payment receipts, and public awareness programs. Public understanding of the policy is relatively good; however, its utilization remains limited. The main challenges include insufficient public awareness, the practice of distributing zakat directly to beneficiaries, and limited socialization regarding the integration of zakat and taxation. Therefore, stronger educational efforts and institutional coordination are needed to enhance the effectiveness of the relationship between zakat and taxation and to maximize its benefits for society.